Frequency distribution of polymorphisms on k-casein and DGAT1 genes in dairy cattle used in Chilean milk production - Levicoy, Daniela; de la Barra, Rodrigo; Carvajal, Andrés M. (Austral Journal of Veterinary Sciences, 2023)
Milk solids are very important to transform milk in dairy products like cheese. Several genes and polymorphic variants had been associated with this process, increasing the milk fat and/or protein content or regulating the coagulation milk properties. In the present study, we evaluate the frequency distribution of two major polymorphisms present in DGAT1 and CSN3 genes in 6 dairy biotypes commonly used in southern Chile: Holstein-Friesian (HF), Jersey (JE), Montbeliarde (MB), Overo Colorado (OC), Frisón Negro (FN) and hybrids (HYB). For CSN3 the results revealed that the A variant was predominant (0.57 to 0.71) in all breeds except Jersey which showed a high frequency of the B variant (0.73), one that favors milk transformation, and in MB (0.58). For DGAT1 a similar trend was seen. The A variant predominated (0.64 to 0.96) in all populations except Jersey, which displayed a high frequency (0.70) of the K variant that favors milk solids. The analysis of FIS for both markers gave negative and non-significant values in all populations some exception of OC and HYB, which are not in Hardy-Weinberg equilibrium, suggesting an excess of heterozygotes. By another hand, FST analysis suggest a high genetic structure for Jersey. The simultaneous analyses of both markers produced 16 combined genotypes with hybrid animals displaying the highest number (11) whereas Jersey showed a favorable combination (DGAT1 KK and CSN3 BB) renewing their productive orientation to transform milk to cheese. Also, some Holstein animals displayed a heterozygous combined genotype (DGAT1 A/K–CSN3 AB). For decades, Holstein-Friesian has been an important breed used for milk production in southern Chile and during the last time, several farmers have introduced Jersey in order to improve milk quality. In this sense, our results show the presence of potential favorable genotypes for the transformation of milk to dairy products.